FEMINISM REFLECTED IN PRIDE AND PREJUDICE NOVEL BY JANE AUSTEN 1813 - Suaidi Suaidi; Rusfandi Rusfandi (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2016)
This thesis analyzes the Pride and Prejudice novel by Jane Austen. The story is about Bannet family. It is interesting to discuss, this novel since it reflects solidarity of family, and the power of woman who always opposed the marriage culture when their got married with a man it is seen when Elizabeth try to contrary her parents mindset especially to all parents in that era. She faces many problems in her life. With all of her ability she can solve it and gain her happiness. This study contains two problems formulation to be analyzed. The first is “What issues of feminism are reflected in the Pride and Prejudice novel?” And the second is “What are the dominant roles of women deserted in the Pride and Prejudice novel?”. The research design of this study is descriptive qualitative method because beside the data are taken from the novel (primary data), the researcher also use secondary data (theories, explanation, different news form about feminism). These secondary data are used to support the result of analysis of the primary data. Finally, the researcher suggests on the findings of Feminism Reflected in the Pride and Prejudice novel by Jane Austen to the readers to comprehend that Pride and Prejudice novel also provide insight to the community to determine the role of women on the early nineteenth century were always viewed as weak and does not have the ability in his capacity as a human being. The results of this study can be used as a reference in the research literature itself in educational institutions and so on. The result of this study is also expected to be useful in several ways. This study gives significance for the researcher to understand and provides more knowledge about feminism. This study may be expected to give significant to the future researchers who conduct studies about literature focusing on feminism or on Pride and Prejudice novel by providing preliminary study.